Leadership standards in action: The school principal as servant leader - Ervin, Candice (Journal of Interdisciplinary Studies in Education, 2015)
Leadership as a school principal can be an arduous task. Despite the laborious mood that a principal may experience, the career is very rewarding. In order for one to know how to become an effective principal he or she must understand and apply certain standards to their professional title. In Cade Brumley’s Leadership Standards in Action: The School Principal as Servant Leader, he discusses and explores the idea of being a servant leader. He explains to readers the idea of servant leadership by utilizing the Interstate School Leaders Licensure Consortium (ISLLC) standards and personal accounts of current principals. Brumley offers an enlightening perspective to current and potential leaders through his creative narration of realistic situations.